Green living room: an exploration of a new domestic space in the urban housing - Rahmani, Ebrahim (My University, 2022)
Living in big cities usually has a lot of advantages which make the cities an attractive place to live in. Normally people immigrate from the countryside to the cities to take part of those benefits. Job opportunities, proper public transportation and broad and compelling social life and activities are only a few of them to be mentioned. However, living in an urban context has its disadvantages as well. Life in big cities usually is associated with limited access to greenery, stress, anxiety and a low standard of living due to obvious reasons. Furthermore, the studies indicate that all these issues are somehow related to each other and affect one another in a direct and sometimes in an indirect manner. Due to the low standard of living and lack of greenery in urban areas people need to deal with a lot of psychological issues more than people in the rural areas. Access to nature and greenery have a direct impact on the well-being of people. According to studies, patients who have been exposed to greenery have had a shorter recovery period than people who have not been exposed to greenery. Moreover, the presence of greenery can reduce the stress level and anxiety of people in the cities caused by air pollution, tension and hecticness. Due to the hectic nature of urban spaces people in the cities are usually facing minor mental and even physical issues. In the other hand, as the positive impact of greenery on the well-being of humankind is no secret, greenery should be an antidote to the modern society issues. The usage of greenery should not be limited to the small area in the courtyard or in the small park in the neighbourhood. It should be valued as a tool for improvement of human health. The aim of this master thesis is to investigate the implementation of greenery in domestic space in order to promote a sustainable way of living in the cities. The focus has been to design a housing typology in an urban context and try to imitate and model housing typologies associated with countryside and rural areas. A housing complex which despite being in a dense part of a city contains the qualities of a villa or single-family housing.